Pengaruh Kompetensi Sumber Daya Manusia, Pengendalian Internal, Moralitas Individu, dan whistleblowing system Terhadap Pencegahan Fraud - Marheni, Ni Luh; Hutnaleontina, Putu Nuniek (Hita Akuntansi dan Keuangan, 2025)
Efforts to avoid fraud are essentially aimed at reduce opportunities for perpetrators, making them vulnerable to misappropriation. By tightening supervision in high-risk areas, the possibility of fraudulent activities can be reduced. This research was conducted at the village office in Pupuan sub-district. Data was collected using a structured questionnaire that was specifically developed to capture and assess each variable accurately. The analysis findings show that human resource capabilities have a positive and significant impact on preventing fraud. Internal control mechanisms also play a positive and significant role. In addition, individual morality has a positive and significant effect on efforts to prevent fraud, and the implementation of a reporting system for violations further strengthens fraud prevention with a positive and significant effect.